2022
DOI: 10.1017/ash.2022.233
|View full text |Cite
|
Sign up to set email alerts
|

Association of antibiotics with veteran visit satisfaction and antibiotic expectations for upper respiratory tract infections

Abstract: Background and objective: Veterans’ Affairs (VA) healthcare providers perceive that Veterans expect and base visit satisfaction on receiving antibiotics for upper respiratory tract infections (URIs). No studies have tested this hypothesis. We sought to determine whether receiving and/or expecting antibiotics were associated with Veteran satisfaction with URI visits. Methods: This cross-sectional study included Veterans evaluated for URI January 2018–December 2019 in an 18-clinic ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Of particular importance is the association between antibiotic prescriptions and repeat respiratory-related 14-day respiratory healthcare contact, which was consistent in the overall, pre-, and postintervention cohorts. Previous studies have documented that antibiotic prescriptions are associated with higher patient satisfaction scores [ 29 , 30 ], particularly if patients enter encounters expecting an antibiotic prescription [ 31 ]. It is possible that lack of antibiotic prescription drove certain patients (ie, the inconvincible patients) [ 32 ] to seek prescriptions elsewhere within the health system, thereby driving repeat contact.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance is the association between antibiotic prescriptions and repeat respiratory-related 14-day respiratory healthcare contact, which was consistent in the overall, pre-, and postintervention cohorts. Previous studies have documented that antibiotic prescriptions are associated with higher patient satisfaction scores [ 29 , 30 ], particularly if patients enter encounters expecting an antibiotic prescription [ 31 ]. It is possible that lack of antibiotic prescription drove certain patients (ie, the inconvincible patients) [ 32 ] to seek prescriptions elsewhere within the health system, thereby driving repeat contact.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] However, recent work by Staub et al found that among patients with respiratory tract infections, receipt of an antibiotic was not independently associated with improved satisfaction. [ 36 ] Instead, they found that receipt of antibiotics had to match the patient’s expectations to affect patient satisfaction and recommended that clinicians communicate with their patients about prescribing expectations. This finding complements our results in the present study and the importance of communication about expectations is similarly important for NSAID prescribing as well.…”
Section: Discussionmentioning
confidence: 99%